Quantum coherent Chladni-like resonance: Programming ions as matter waves for subpicosecond conduction - Yaren Sezen; Niyazi Okan Çiftçi; Mehmet Ali Sarsıl; Kamil Czelej; Onur Ergen (Proceedings of the National Academy of Sciences, 2026)
Achieving coherent control of ionic transport in solids, analogous to electron waveguides, remains a fundamental challenge, as ionic motion is typically limited by slow, stochastic hopping. Here, we demonstrate that a two-dimensional electrochemical cell (borophene/h-BN/graphene) possesses a collective ionic eigenmode, which, when resonantly excited by a “critical-frequency” electrical pulse (10 kHz), transforms ionic conduction from diffusive drift into a coherent, ballistic wave. Time-resolved pump–probe spectroscopy directly reveals this transition through the emergence of a strong 28 THz oscillation, a spectroscopic fingerprint of subpicosecond, wavelike motion. The entire intercalated ion ensemble moves in phase, traversing the 80 nm channel as a coherent wave packet in under 300 fs, corresponding to >1,000-fold speed enhancement over classical diffusion. Leveraging this resonant control principle, we realize an electrochemical device that can be charged in picoseconds with a laser pulse. This work demonstrates that quantum-level, Chladni-like resonance is achievable for ionic matter, establishing a universal pathway to programmable, ultrafast coherent ionic conduction. By transforming ions from disordered particles into controllable matter-waves, we unlock the field of coherent ionics for picosecond-scale energy storage and neuromorphic computing.